And we didn’t even have to pay them! Library Days for Faculty and Graduate Students. - Kearns, Sara K. (My University, 2010)
Faculty and graduate students may see the value in learning how to use library resources and tools more effectively, but they can rarely carve out the time. Kansas State University Libraries responded by developing Library Days. Library Days are scheduled like conferences, with many concurrent sessions offered throughout the day. Faculty and graduate students can then attend a line-up of classes according to their needs. Stop by and learn about the logistics and benefits of creating your own Library Day.
Keywords: Library instruction